2014
DOI: 10.1007/s00216-014-8240-7
|View full text |Cite
|
Sign up to set email alerts
|

“Fooling fido”—chemical and behavioral studies of pseudo-explosive canine training aids

Abstract: Genuine explosive materials are traditionally employed in the training and testing of explosive-detecting canines so that they will respond reliably to these substances. However, challenges arising from the acquisition, storage, handling, and transportation of explosives have given rise to the development of "pseudo-explosive" training aids. These products attempt to emulate the odor of real explosives while remaining inert. Therefore, a canine trained on a pseudo-explosive should respond to its real-life anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…2-Ethyl-1-hexanol also registers among the most telltale compounds, and is a known hydrolysis product of the plasticizers bis(2-ethylhexyl) phthalate, bis(2-ethylhexyl) adipate, bis(2-ethylhexyl) sebacate. [13][14][15][16] In a number of products, the 2-ethylhexyl moiety is present in the form of benzoic acid 2-ethylhexyl ester, suggesting a possible source of origin.…”
Section: Resultsmentioning
confidence: 99%
“…2-Ethyl-1-hexanol also registers among the most telltale compounds, and is a known hydrolysis product of the plasticizers bis(2-ethylhexyl) phthalate, bis(2-ethylhexyl) adipate, bis(2-ethylhexyl) sebacate. [13][14][15][16] In a number of products, the 2-ethylhexyl moiety is present in the form of benzoic acid 2-ethylhexyl ester, suggesting a possible source of origin.…”
Section: Resultsmentioning
confidence: 99%
“…These canines did not reliably respond to authentic Composition C-4. Conversely, canines imprinted on authentic Composition C-4 did not reliably respond to either of the training aids [2].…”
Section: Sample Quantities Used In Our Canine Trialmentioning
confidence: 98%
“…A 25 critical aspect of successful canine detection relies on well-controlled initial and 26 maintenance training protocols. For example, Kranz et al [1,2] recently reported that 27 canines varied in performance when trained using different training materials. However, 28 use of contraband materials as training materials requires care in storage and chain-of-29 custody.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative training aid materials (often termed pseudo-, mimic, or simulant 30 training aids) contain the characteristic odorants of the hazardous materials, but in a form hazardous materials [3]. Although the use of non-explosive training aids as replacements 1 for real explosives have yet to be widely accepted by the canine detection community, the 2 development of these alternative training aids would greatly facilitate canine training. 3 Developing alternative training materials not only requires presenting the key 4 characteristic odors, but also requires knowledge about the longevity of the odor release 5 by the training aid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation